Experimental study on heat transfer augmentation of graphene based ferrofluids in presence of magnetic field. (5th March 2017) - Sadeghinezhad, Emad; Mehrali, Mohammad; Akhiani, Amir Reza; Tahan Latibari, Sara; Dolatshahi-Pirouz, Alireza; Metselaar, Hendrik Simon Cornelis; Mehrali, Mehdi
Graphical abstract: Highlights: Synthesizing graphene based ferrofluids with high colloidal stability. Investigation of thermo-physical and magnetic properties. Investigation of the forced convective heat transfer in presence of magnetic field. The local convective heat transfer was enhanced up to 82%. Abstract: The effect of a permanent magnetic field on the heat transfer characteristics of hybrid graphene-magnetite nanofluids (hybrid nanofluid) under forced laminar flow was experimentally investigated. For this purpose, a reduced graphene oxide-Fe3 O4 was synthesized by using two-dimensional (2D) graphene oxide, iron salts and tannic acid as the reductant and stabilizer. Graphene sheets acted as the supporting materials to enhance the stability and thermal properties of magnetite nanoparticles. The thermo-physical and magnetic properties of this hybrid nanofluid have been widely characterized and it shows that the thermal conductivity increased up to 11%. The hybrid nanofluid behaves as a Newtonian fluid with liquid like behavior with superparamagnetic properties as was evident from its magnetic saturation value at 45.9 emu/g. Moreover, the experimental heat-transfer results indicated that the heat transfer enhancement of the hybrid nanofluid compared to the control fluid (distilled water) was negligible when no magnetic field was applied. Additionally, the convective heat transfer was significantly improved under the influence of a magnetic field with a maximum enhancement of 82% in terms of the convective heat transfer properties of the hybrid nanofluid.